Capital Income Risk and the Dynamics of the Wealth Distribution - Hoang Khieu; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2019)
Labour income follows a deterministic growth trend and fluctuates between two values. Interest rates are drawn initially, fluctuate between two values and can differ in their arrival rates. Low interest rates imply a stationary long-run wealth distribution, high interest rates imply exploding wealth dynamics. When matching the NLSY 79 evolution of the wealth distribution from 1986 to 2008, we obtain a fit of 96:1%: With a more flexible interest rate distribution, employing "superstar states", the fit can increase to 96:7%. For the fit of 96:1%, the standard deviation of model returns is much lower than the empirical standard deviation.
Keywords: C60; D30; E20; 330; dynamics of wealth distributions; NLSY 1979 cohort; capital income risk; Fokker-Planck equations